2018
DOI: 10.1016/j.arabjc.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Free fluoride determination in honey by ion-specific electrode potentiometry: Method assessment, validation and application to real unifloral samples

Abstract: Surprisingly, a reliable method for measuring the concentration of free fluoride ions in honey is still missing from the literature, notwithstanding the generally recognized importance of the analyte and the matrix. To fill this gap, this study proposes and validates a straightforward ion-specific electrode potentiometric method for this task. The method offers very low detection and quantification limits (6.7 lg kg À1 and 25 lg kg À1 , respectively), good linearity (R 2 > 0.994), good sensitivity (typically 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…This is also evident from the calibration curve (Figure 1) and even more so from the comparison of the fluoride content obtained when calculating the results of the dp-AcB_DS and dp-TISAB_DS used, which were 9.5% and 5.4%, respectively (Figure 3). This is consistent with the conclusions of numerous groups of authors proposing TISAB as the optimal buffer for fluoride determination [35][36][37]. Additionally, the higher values of fluoride concentration in the tested wine samples obtained with dp-TISAB_DS (0.19 mg/L) compared to the results obtained with dp-AcB_DS (0.16 mg/L) are logically due to chelation [36].…”
Section: Buffer Influence In Fluoride Determinationsupporting
confidence: 91%
See 1 more Smart Citation
“…This is also evident from the calibration curve (Figure 1) and even more so from the comparison of the fluoride content obtained when calculating the results of the dp-AcB_DS and dp-TISAB_DS used, which were 9.5% and 5.4%, respectively (Figure 3). This is consistent with the conclusions of numerous groups of authors proposing TISAB as the optimal buffer for fluoride determination [35][36][37]. Additionally, the higher values of fluoride concentration in the tested wine samples obtained with dp-TISAB_DS (0.19 mg/L) compared to the results obtained with dp-AcB_DS (0.16 mg/L) are logically due to chelation [36].…”
Section: Buffer Influence In Fluoride Determinationsupporting
confidence: 91%
“…In the first phase of the research, the influence of the composition of the solution on the FISE response was studied by direct potentiometry. Since some groups of authors used acetate buffer [33,34] while others suggested TISAB as optimal for fluoride determination [35][36][37], both were investigated in this study by comparing their influence on fluoride determination. Evaluation of the direct potentiometry method and the standard addition method in the determination of fluoride was also performed.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, this protocol is currently absent in the literature. Hence, pursuing the interest of this research group in the development and validation of original FISE methods applicable either in dental research [ 57 , 65 , 66 , 67 , 68 ] or in food analysis [ 69 ], the aim of this study is to develop for the first time (and validate, where possible) a comprehensive analytical protocol for the FISE determination of the fluorine contained in different fractions of bovine milk.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, excessive fluoride intake can lead to human poisoning, 3 and there is a small gap between a safe dose and a harmful one 4 . According to Regulation 98/83/EEC of the Council of the European Communities, the fluoride content of drinking water is required to be less than 1.5 μg/mL 5 . In view of the ubiquity of fluorides, it is of great significance to determine the content of fluoride ion in drinking water, surface water and sewage, for the purpose of environmental protection and people's health 6 …”
Section: Introductionmentioning
confidence: 99%